The Importance of Primary Care Psychiatry - Brahmavar Nagesh Pai MBBS, DPM, DNB (Psych); Shae-Leigh Cynthia Vella BPSYC (Hons) (SAGE Publishing, 2011)
This paper provides a review of the importance of primary care psychiatry within an Australian context. The aims of this review are: (1) to emphasize the integral role of mental health in overall health and well-being, (2) to elucidate the factors that make the provision of primary care psychiatry essential, and (3) to review the impact of the Australian government's mental health policy initiatives on the mental health of the Australian population as well as on the practice of primary care psychiatry. From this review, it is evident that the discipline of psychiatry is integral to the overall health of the community. Furthermore, it is apparent that primary care psychiatry has a large and pivotal role to play in the prevention, treatment, and early detection of mental disorders in Australia and worldwide. The article concludes with some simple, actionable recommendations for the practice of primary care psychiatry.